Electric energy : an introduction - El-Sharkawi, Mohamed A. (Power electronics and applications series., 2013)
"Along with the standard topics of power electronics and electromechanical conversion, this popular text covers energy resources, power plants, environmental impacts of power generation, power system operation, renewable energy, and electrical safety. Focusing on issues encountered daily in practice, the author includes examples based on real systems and data. Now in color, this third edition offers new and expanded coverage on the failure modes of nuclear power plants, interface and integration issues, stray voltage and impulse shocks, the circuits in wind and solar systems, and smart grid technology"--